The Instrumental Activities of Daily Living in Parkinson’s Disease Patients Treated by Subthalamic Deep Brain Stimulation - Bezdicek, Ondrej; Mana, Josef; Růžička, Filip; Havlik, Filip; Fečíková, Anna; Uhrová, Tereza; Růžička, Evžen; Urgošík, Dušan; Jech, Robert (Frontiers in Aging Neuroscience, 2022)
Background: Everyday functioning and instrumental activities of daily living (IADL) play a vital role in preserving the quality of life in patients with Parkinson’s disease (PD) after deep brain stimulation of the subthalamic nucleus (STN-DBS). Objective: The main goal of the current study was to examine IADL change in pre-and post-surgery of the STN-DBS. We also analysed the influence of the levodopa equivalent daily dose (LEDD) and global cognitive performance (Dementia Rating Scale; DRS-2) as covariates in relation to IADL. Methods: Thirty-two nondemented PD patients were administered before and after STN-DBS neurosurgery the Penn Parkinson's Daily Activities Questionnaire (PDAQ; self-report), the DRS-2 and Beck Depression Inventory (BDI-II) to assess IADL change, global cognition and depression. Results: We found a positive effect of STN-DBS on IADL in the post-surgery phase. Moreover, lower global cognition and lower LEDD are predictive of lower IADL in both pre-surgery and post-surgery examinations. Summary/Conclusion: STN-DBS in PD is a safe method for improvement of everyday functioning and IADL. In the post-surgery phase, we show a relation of IADL to the severity of cognitive impairment in PD and to LEDD.